Spatial Lymphocyte Dynamics in Lymph Nodes Predicts the Cytotoxic T Cell Frequency Needed for HIV Infection Control - Grebennikov, Dmitry; Bouchnita, Anass; Volpert, Vitaly; Bessonov, Nikolay; Meyerhans, Andreas; Bocharov, Gennady (Frontiers in Immunology, 2019)
The surveillance of host body tissues by immune cells is central for mediating their defense function. In vivo imaging technologies have been used to quantitatively characterize target cell scanning and migration of lymphocytes within lymph nodes (LNs). The translation of these quantitative insights into a predictive understanding of immune system functioning in response to various perturbations critically depends on computational tools linking the individual immune cell properties with the emergent behavior of the immune system. By choosing Newtonian second law for the governing equations, we developed a broadly applicable mathematical model linking individual and collective T cell behaviors. The spatial cell dynamics is described by a superposition of autonomous locomotion, intercellular interaction and viscous damping processes. The model is calibrated using in vivo data on T cell motility metrics in LNs such as the translational speeds, turn speeds, and meandering indices. The model is applied to predict the impact of T cell motility on protection against HIV infection, i.e., to estimate the threshold frequency of HIV-specific CTLs which is required to detect productively infected cells before the release of viral particles starts. Finally, it provides further guidance for HIV vaccine studies allowing for the migration of cells in fibrotic LNs.